Inhibitory effect of liposome-encapsulated anthocyanin on melanogenesis in human melanocytes. (August 2013) - Hwang, Jin-Ming; Kuo, Hsing-Chun; Lin, Ching-Ting; Kao, Erl-Shyh
Abstract Context: Melanin plays an important role in preventing ultraviolet (UV) light-induced skin damage. Overexposure to UV radiation can lead to the formation of free radicals and trigger inflammation and hyperpigmentation of the skin. Anthocyanin can combat excessive free radicals in the body and can reduce the occurrence of inflammation. However, anthocyanin molecules are unstable and highly susceptible to degradation. Objective: The present study aims to elucidate the effects of liposome-capsulated anthocyanin (LCA) from Hibiscus sabdariffa Linn. on melanogenesis in human A375 melanocytes. Materials and methods: The effects of LCA with various doses (5–50 mg/mL) on cell viability, melanin content, tyrosinase activity, expression of the tyrosinase and microphthalmia-associated transcription factor (MITF) were measured. Results: Anthocyanin exhibits scavenging activity on DPPH radical with the inhibitory rate of 11 and 24% at 20 and 50 mg/mL concentration treatment, respectively, and inhibitory effects on melanin production by 8, 14, 23 and 30% at 5, 10, 20 and 50 mg/mL concentration treatment, respectively. However, LCA has enhanced DPPH scavenging activity (64 and 76% at 20 and 50 mg/mL concentration treatment, respectively) and inhibitory effects against melanin synthesis (23, 35, 43 and 60% at 5, 10, 20 and 50 mg/mL concentration treatment, respectively). Moreover, anthocyanin-inhibited melanin synthesis occurs through the inhibition of tyrosinase enzymatic activity and suppression of the protein expression of tyrosinase and MITF. Discussion and conclusion: Liposome encapsulation increases the stabilization of anthocyanin and the inhibition of melanogenesis. Our findings indicate that LCA may be suitable as a photoprotective agent for the skin.